The Role of Attraction, Staff Service, Information, Facilities, and Quality of Activities in Increasing Revisit Intention through Tourist Satisfaction of to Sea World Ancol Visitors - Fauzan Kamil Akbar; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of attraction, staff service, information, facilities, and quality of activities on the revisit intention of Sea World Ancol visitors through the mediating role of tourist satisfaction, drawing on the expectancy confirmation theory (ECT) framework. This quantitative study employed a survey method with a nonprobability purposive sampling technique, targeting visitors who had visited Sea World Ancol within the past six months. Data were collected through an online questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3.2.9. Of the eleven hypotheses proposed, seven were supported by empirical findings. The results indicate that attraction, staff service, and information each exert a direct and significant effect on tourist satisfaction, which in turn exerts a direct and highly significant effect on revisit intention, whereas facilities and quality of activities exert a positive but non-significant effect on tourist satisfaction. Furthermore, tourist satisfaction was found to mediate the effects of attraction, staff service, and information on revisit intention, while its mediating role for facilities and quality of activities was not statistically supported. These findings offer theoretical and practical contributions by extending the application of expectancy confirmation theory to the context of indoor marine edutainment tourism and by demonstrating that the mediating role of satisfaction is conditional on the strength of an attribute's direct effect, while also providing practical guidance for Sea World Ancol's management to prioritize attraction renewal, staff service enhancement, and information expansion as key strategies for strengthening tourist satisfaction and encouraging repeat visitation.